2021
DOI: 10.1007/978-981-33-6893-4_98
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Frequency Reconfigurable Flexible Antenna for 5Gsub-6-GHz and ISM Band Applications

Abstract: This paper presents the design and characterization of on-demand frequency reconfigurable antenna for 5Gsub-6-GHz and ISM-band applications. The antenna comprises of compact overall size having dimensions of 0.23λ 0 × 0.2λ 0 × 0.002λ 0 . The octagonal patch was loaded with stub to enhance bandwidth along with improvement in return loss, afterword a slot and diode was utilized to achieve frequency reconfigurability. The numerical analysis of the proposed antenna was done using Higher Frequency Structural Simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The proposed patch antenna for future communications is presented with electromagnetic simulation based on the wave iterative method (WCIP) algorithm. The design methodology was initiated by designing a compact conventional microstrip antenna for 118.87 GHz, and the equations to find the parameters of the antenna are presented in the following paper [12], then the antenna was miniaturized until we found the proposed antenna in Fig. 4, by increasing the rectangular slots, so that the antenna covers the spectrum of the 118.87 GHz band distributed in the world for future applications.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed patch antenna for future communications is presented with electromagnetic simulation based on the wave iterative method (WCIP) algorithm. The design methodology was initiated by designing a compact conventional microstrip antenna for 118.87 GHz, and the equations to find the parameters of the antenna are presented in the following paper [12], then the antenna was miniaturized until we found the proposed antenna in Fig. 4, by increasing the rectangular slots, so that the antenna covers the spectrum of the 118.87 GHz band distributed in the world for future applications.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Moreover, when one wishes to simulate complex structures (from the point of view of geometry), it is necessary to make a discretization (differential methods) or to define a set of test functions (integral methods) that can limit the use of these test functions. Nevertheless, to support the exponential increase in the number of users, the next generation of communication systems will need to use high data rates and be low cost and efficient, as shown in [8][9][10][11][12]. The THz regime is one of the continuing challenges facing materials technology and the development of electronic and photonic devices [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…An antenna array was developed for 5G systems by orienting four antenna elements on a 3D profile and separated with MTM defects; such an antenna provided a high gain-bandwidth product. However, the proposed antenna in [ 18 ] was very complicated and not applicable with low-profile devices [ 19 ]. Moreover, another design was proposed in [ 20 ] based on a reconfigurable antenna element with optical switches but without considering the array systems analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [20] reported that the antenna's gain decreases as the OAM mode order increases. In regards to flexible antenna for 5G sub-6 GHz bands, the authors in [21] designed and simulated a reconfigurable antenna to operate at four different frequency bands. The gain obtained at 2.45, 3.85 and 3.2 GHz was 1.8, 2.9 and 2.78 dBi respectively.…”
Section: Introductionmentioning
confidence: 99%